Equivalence of many-photon Green's functions in the Duffin-Kemmer-Petiau and Klein-Gordon-Fock statistical quantum field theories - Valverde, J. S.; Pimentel, B. M.; Fainberg, V. Y. (Consultants Bureau, 2004)
Using the functional integral formalism for the statistical generating functional in the statistical (finite temperature) quantum field theory, we prove the equivalence of many-photon Greens functions in the Duffin-Kennner-Petiau and Klein-Gordon-Fock statistical quantum field theories. As an illustration, we calculate the one-loop polarization operators in both theories and demonstrate their coincidence.
Keywords: statistical field theory; photon Green's functions; path integral; renormalization; equivalency